Analisis excess return pada perusahaan MNC36 dengan Fama French Model tiga faktor - Yasir Maulana; Puji Lestari (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2025)
This research examines excess returns using the three-factor Fama-French model (market risk, size, and book-to-market ratio) on stocks of MNC36 index businesses listed on the Indonesia Stock Exchange (IDX) over the 2020-2022 timeframe. This research used purposive sampling to choose a population of 55 firms, resulting in a sample of 19 enterprises. The analytical methods used are descriptive analysis and verification analysis using panel data regression analysis. All variables in this research satisfy the traditional assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation. The panel data regression findings indicate the impact of market risk, size, and book-to-market ratio on excess return. The hypothesis test concludes that the three factors together influence excess returns.